The Authority of Kyai Toward the Santri: A Review of Gender Construction at Pondok Pesantren - Pramono, Didi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
The purpose of the study are assess the perception of Kyai and students about the gender construction, analyze the power of Kyai in forming gender construction, analyzing the social interactions between Kyai, students, and society. This study used a qualitative approach, with research location is in Al-Hikmah 2 Benda Boarding School Sirampog District, Brebes. Conclusions of the study are Kyai and students have moderate views on the construction of gender, but in practice it is still ambiguous because it could not distinguish between nature and gender. This perception creates stereotypes that lead to the injustices against women, including subordination, marginalization, and the double burden in terms of access, participation, control, and benefits. Gender construction in boarding school reinforced by Kyai’s position in a dialectical process of externalization, objectification, and internalization. The patron-client relationship between Kyai, students, and society further strengthen the position of Kyai as a significant other in the process of gender construction in boarding school.